FUNGSI ITIKAD BAIK DALAM PERJANJIAN PINJAM MEMINJAM UANG PADA KOPERASI SERBA USAHA KALIANUSA DI TINJAU DARI PASAL 1338 AYAT (3) KITAB UNDANG - UNDANG HUKUM PERDATA - Muhammad Gunarso (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The function of good faith is very important because to restrict the arbitrary action against others who are vigilant and then to provide legal protection to the honest parties in the implementation of the agreement. Both parties must be acting in good faith in implementing the agreement. There are times when good faith has been fully carried out and considered, but the implementation of the agreement is still in deadlock (deadlock). This is where the attention is required towards compliance so that an event can be completed satisfactorily. Of course, as with all the goods things that contain award (waardering), compliance is not likely to result in a settlement of events that satisfy every man, but always is not absolute (relatief), which is worth in the thoughts and feelings of the people in charge of solving a events, such as the Judge or the Administration after the notice of all the factors, which can be used in the minds and feelings of the nature of it. With good faith and trust both parties. Then occurred close relationship between the doctrine of good faith in the implementation of the agreement and the theory of confidence at the time of the agreement. The good faith (Article 1338, paragraph 3) and appropriateness (Article 1339) is generally mentioned in the same breath, if the judge after examining the appropriateness of an agreement can not be implemented then it means that the agreement was contrary to public order and decency. Agreement is not only determined by the parties in the formulation of the agreement, but also determined by the good faith and decency, so in good faith and decency were also determines the content of the agreement. Thus a particular treaty agreement borrowing money if implemented not in good faith (in bad faith), then the agreement is contrary to public order and morality and legal norms in force. And the parties to the treaty shall avoid the execution of the agreement in bad faith. It happens then the harmed can file a judicial directive and protected by law.